Attitudes Constraining the Inclusion of People with Disabilities in a Ghanaian Public University: Student and Staff Perspective - Mensah, Mary Afi (European Scientific Journal, ESJ, 2022)
Attitudes are fundamental to the inclusion of students with disabilities in higher education. This study explored the perspectives of students and staff regarding the attitudes that hinder the inclusion of students with disabilities in a Ghanaian university. A qualitative methodology was employed, with data collected through interviews with 13 respondents, including seven university lecturers and six students with disabilities. These data were analysed and presented thematically. From the perspective of these respondents, the attitudes that influence the inclusion of students with disabilities in the university community are: preconceived ideas and mindsets, offensive remarks and comments, and undesirable patterns of behaviour and actions. It was recommended that tools such as comprehensive awareness raising, continuous contact and participation in university activities, and integrating attitudes and beliefs into professional preparation and development programmes be used to combat these negative attitudes. It was concluded that the identification and implementation of programmes, guidelines, and procedures that may bring about fundamental attitudinal change are essential for successfully including people with disabilities in higher education institutions (HEIs).